Nidificación de meliponinos (Hymenoptera: Apidae) de la Región Central de Colombia - Vergara B., Carlos; Villa L., Antonio; Nates P., Guimar (Revista de Biología Tropical, 1986)
Field observations of 34 species of stingless bees in 303 nests in Cundinamarca, Colombia, included the following parameters: construction site, presence or absence of a specialized entrance structure, degree of exposure, heigth of nest above the ground and altitudinal distribution. A trend to nest in live trees, usually with a especialized entrance structure was found. Most species build unexposed nests.